2018
DOI: 10.1038/s41593-018-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortico–reticulo–spinal circuit reorganization enables functional recovery after severe spinal cord contusion

Abstract: Severe spinal cord contusions interrupt nearly all brain projections to lumbar circuits producing leg movement. Failure of these projections to reorganize leads to permanent paralysis. Here we modeled these injuries in rodents. A severe contusion abolished all motor cortex projections below injury. However, the motor cortex immediately regained adaptive control over the paralyzed legs during electrochemical neuromodulation of lumbar circuits. Glutamatergic reticulospinal neurons with residual projections below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
310
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(321 citation statements)
references
References 56 publications
9
310
1
1
Order By: Relevance
“…Corresponding observations in rats were reported on the role of the RST in functional recovery in rodents after either cortical lesion (Bachmann et al., ) or spinal cord lesion (Ballermann & Fouad, ; Filli et al., ; Garcia‐Alias, Truong, Shah, Roy, & Edgerton, ; Zörner et al., ). In a rat model of spinal cord contusion, it was demonstrated that a reorganization of the cortico‐reticulo‐spinal circuit enabled functional recovery of walking and swimming (Asboth et al., ). Studies on mice showed that after stroke of the sensorimotor cortex there was an increase of the CST and RST projections as well as corticoreticular projections, with projections from RST six times stronger than those from CST (Bachmann et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding observations in rats were reported on the role of the RST in functional recovery in rodents after either cortical lesion (Bachmann et al., ) or spinal cord lesion (Ballermann & Fouad, ; Filli et al., ; Garcia‐Alias, Truong, Shah, Roy, & Edgerton, ; Zörner et al., ). In a rat model of spinal cord contusion, it was demonstrated that a reorganization of the cortico‐reticulo‐spinal circuit enabled functional recovery of walking and swimming (Asboth et al., ). Studies on mice showed that after stroke of the sensorimotor cortex there was an increase of the CST and RST projections as well as corticoreticular projections, with projections from RST six times stronger than those from CST (Bachmann et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We are still rudimental in our understanding of how rehabilitation influences regeneration, neuroplasticity and motor recovery following SCI. Several studies reported exercise-induced plasticity of various spinal tracts, particularly the serotonergic and reticulospinal tracts (Engesser-Cesar et al, 2007;Asboth et al, 2018;Loy et al, 2018). Conversely, an equalling number reported no such ability and proposes the role of rehabilitation in shaping newly formed connections by spontaneous mechanisms or plasticity-promoting treatments (Garcia-Alias et al, 2009;Maier et al, 2009;Wang et al, 2011a;Alluin et al, 2014).…”
Section: Remyelinationmentioning
confidence: 99%
“…Since neural activity can facilitate OPC‐axon contact through vesicular glutamate release, it is theorized that glutamate plays a role in neuromodulation‐induced locomotion. Indeed, stimulating murine brainstem glutamatergic neurons in conjunction with gravity‐assisted rehabilitation promotes extensive reorganization of neural projections, ultimately leading to long lasting motor recovery, even when epidural stimulation is discontinued (Asboth et al, ). Perhaps neuromodulation allows electrically silent neurons/axons to regain activity‐induced glutamate release after SCI.…”
Section: Additional Factors To Consider In Opc Responses and Myelinatmentioning
confidence: 99%